CROSS-CULTURAL DIFFERENCES THAT OCCURRED DURING THE TRIP PROVIDED BY MALANG TOURISM INFORMATION CENTER AND STRATEGIES TO COPE WITH IT - Azizah Syafiqoh Az-Zahra; Angkita Wasito Kirana (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
This study aimed to find out what were the types of cross-cultural differences that occurred during the open-trip services that was provided by Malang Tourism Information Center and how the tour guides deal with it. The research was conducted by observing the interaction of the tour guide and the guests during the trip. The observation was conducted for three months from January to March 2020. The participants of this research were a female tour guide and several foreign guests that came from several different countries. The data showed that cross-cultural differences that occurred were in the form of Ethnic Culture, Universal Culture, and Individual Culture. Language and punctuality became the most obvious barriers as the guests sometimes did not share similar language for communication as well as similar point of view about the punctuality. The tour guides used listening and respecting differences strategies to cope with the conflicts that occurred. These two methods were also effective in preventing problems due misunderstanding that were caused by the cross-cultural differences.